Pediatric psychiatric emergency rooms during COVID-19: a multi-center study - Galit Erez; Sol Yakubovich; Hadar Sadeh; Gal Shoval; Gila Schoen; Gal Meiri; Nimrod Hertz-Palmor; Tali Butler; Yael Barzilai; Mariela Mosheva; Doron Gothelf; Yuval Bloch (BMC Psychiatry, 2022)
Abstract Background The COVID-19 (SARS-CoV-2) pandemic has been a major stressor for the mental health and well-being of children and adolescents. Surveys and reports from hotlines indicate a significant rise in mental health problems. As the psychiatric emergency room (ER) is a first-line free-of-charge facility for psychiatric emergencies, we expected to see a significant increase in visits, specifically of new patients suffering from anxiety, depression, or stress-related disorders. Methods Data from two psychiatric hospital ERs and one general hospital were included. All visits of children and adolescents from the computerized files between March and December of 2019 were analyzed anonymously and compared to the same months in 2020, using multilevel linear modeling. Results There was a significant decline in the total number of visits (p = .017), specifically among those diagnosed as suffering from stress-related, anxiety, and mood disorder groups (p = .017), and an incline in the proportion of visits of severe mental disorders (p = .029). Discussion The limited use of child and adolescent psychiatric emergency facilities during the pandemic highlights the importance of tele-psychiatry as part of emergency services. It also suggests the importance of the timeline of the emergence of clinically relevant new psychiatric diagnoses related to the pandemic. Future studies are needed to establish the long-term effects of the pandemic and the expeditious use of tele-psychiatry.